Design and implementation of a synthetic pre-miR switch for controlling miRNA biogenesis in mammals. Issue 22 (28th September 2017) - Atanasov, Janina; Groher, Florian; Weigand, Julia E.; Suess, Beatrix
Abstract: Synthetic RNA-based systems have increasingly been used for the regulation of eukaryotic gene expression. Due to their structural properties, riboregulators provide a convenient basis for the development of ligand-dependent controllable systems. Here, we demonstrate reversible conditional control of miRNA biogenesis with an aptamer domain as a sensing unit connected to a natural miRNA precursor for the first time. For the design of the pre-miR switch, we replaced the natural terminal loop with the TetR aptamer. Thus, the TetR aptamer was positioned close to the Dicer cleavage sites, which allowed sterical control over pre-miR processing by Dicer. Our design proved to be highly versatile, allowing us to regulate the biogenesis of three structurally different miRNAs: miR-126, -34a and -199a. Dicer cleavage was inhibited up to 143-fold via co-expression of the TetR protein, yet could be completely restored upon addition of doxycycline. Moreover, we showed the functionality of the pre-miR switches for gene regulation through the interaction of the respective miRNA with its specific target sequence. Our designed device is capable of robust and reversible control of miRNA abundance. Thus, we offer a novel investigational tool for functional miRNA analysis.